2005
DOI: 10.1128/mcb.25.1.206-219.2005
|View full text |Cite
|
Sign up to set email alerts
|

Core Promoter Binding by Histone-Like TAF Complexes

Abstract: A major function of TFIID is core promoter recognition. TFIID consists of TATA-binding protein (TBP) and 14 TBP-associated factors (TAFs). Most of them contain a histone fold domain (HFD) that lacks the DNAcontacting residues of histones. Whether and how TAF HFDs contribute to core promoter DNA binding are yet unresolved. Here we examined the DNA binding activity of TAF9, TAF6, TAF4b, and TAF12, which are related to histones H3, H4, H2A, and H2B, respectively. Each of these TAFs has intrinsic DNA binding activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 40 publications
1
72
0
Order By: Relevance
“…Photocrosslinking studies revealed that the DPE is in close proximity to the TFIID subunits TAF6 (TAFII60) and TAF9 (TAFII40), which contain histone fold motifs and are related to histones H4 and H3 [28]. It is thus possible that the TAF6-TAF9 subunits of TFIID interact with the DPE in a manner that is similar to binding of histones H3-H4 to DNA in nucleosomes [29].…”
Section: The Dpe and Mtementioning
confidence: 99%
“…Photocrosslinking studies revealed that the DPE is in close proximity to the TFIID subunits TAF6 (TAFII60) and TAF9 (TAFII40), which contain histone fold motifs and are related to histones H4 and H3 [28]. It is thus possible that the TAF6-TAF9 subunits of TFIID interact with the DPE in a manner that is similar to binding of histones H3-H4 to DNA in nucleosomes [29].…”
Section: The Dpe and Mtementioning
confidence: 99%
“…In addition certain TAF subcomplexes have been reported to specifically bind different core promoter elements. The TAF1⅐TAF2 complex binds to the Initiator element (14) and Drosophila TAF6 and TAF9 crosslinked to the downstream promoter element in the context of TFIID (15), and, as a reconstituted complex, these were shown to associate with a downstream promoter element-containing promoter (16).…”
mentioning
confidence: 99%
“…Second is that both are sites of known ␤-thalassemia point mutations (16,17,36). Third is that TAF9, in combination with TAF6, is thought to interact with promoters that contain these elements (7,8). As a result, we used gel-shift assays to directly test whether TAF9 can interact with any of these regions.…”
Section: Taf9 Directly Binds To the ␤-Globinmentioning
confidence: 99%
“…Of particular relevance are promoters that contain important sequence elements that lie downstream of the transcription initiation site (1,2,6). Mammalian TAF1, TAF9, TAF6, TAF4b, and TAF12 all contact DNA (7). But more specifically, TAF9 is thought to play a role in transcriptional initiation at promoters that contain an imprecisely characterized sequence called the downstream promoter element (DPE), located at around ϩ30 (defining transcription initiation as ϩ1) (1).…”
mentioning
confidence: 99%